Reversible multi-electron storage in dual-site redox-active supramolecular cages - Plessius, Raoul; Orth, Nicole; Ivanovic-Burmazovic, Ivana; Siegler, Maxime A.; Reek, Joost N. H.; Van Der Vlugt, Jarl Ivar (Chemical Communications, 2019)
M6L412+ supramolecular cages 3a and 3b (M = Pd, Pt), soluble in organic solvents, contain two different ligand-centered redox sites that enable the reversible storage of up to 16 electrons, as probed by CV, UV/vis spectro-electrochemistry (SEC-UV/Vis), bulk electrolysis and EPR. Encapsulation of a B12F122- anion is confirmed by 1H, 19F NMR and 19F DOSY NMR spectroscopy and mass spectrometry.
CRIS-Team Scopus Importer:2019-10-29